THE IMPORTANCE OF PRAGMATICS IN DEVELOPING STUDENTS' COMMUNICATIVE COMPETENCE - Makhmudova Nigoraxon boykozi kizi (Bright Mind Publishing, 2025)
This article presents some thoughts on the importance of pragmatics in developing students' communicative competence. Today's modern language teaching is based on the implementation of meaningful, contextual and socially significant communication, and it is through communicative competence that students have the opportunity to conduct effective, culturally appropriate and contextual communication in another language.
Keywords: Communicative competence, pragmatics, language teaching, foreign language, attitude, educational process, principle.